2017
DOI: 10.1539/joh.16-0089-oa
|View full text |Cite
|
Sign up to set email alerts
|

Di-n-butyl phthalate induced hypospadias relates to autophagy in genital tubercle via the PI3K/Akt/mTOR pathway

Abstract: Objective:To explore the mechanisms of hypospadias induced by in utero exposure to din-butyl phthalate (DBP ) . Methods : Timed-pregnant SpragueDawley rats were administered 750 mg / kg of DBP by gavage from GD (gestation days) 13 to GD 18, whereas control group received corn oil. Genital tubercles (GTs) and blood samples were collected from male fetuses on GD 19. The serum testosterone concentration, apoptosis activity, autophagosomes and their related proteins (light chain 3 (LC3-I, LC3-II) ), and sequestoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Similarly, Li et al. also observed that the LC3II/LC3I ratio was significantly increased, and the expression of polyubiquitin‐binding protein p62 was significantly decreased in the GT from the hypospadias male fetuses [29], indicating that exposure to DBP during pregnancy inhibited cell apoptosis and promoted cell autophagy in the GT of fetal male rats, thereby resulting in the formation of hypospadias.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, Li et al. also observed that the LC3II/LC3I ratio was significantly increased, and the expression of polyubiquitin‐binding protein p62 was significantly decreased in the GT from the hypospadias male fetuses [29], indicating that exposure to DBP during pregnancy inhibited cell apoptosis and promoted cell autophagy in the GT of fetal male rats, thereby resulting in the formation of hypospadias.…”
Section: Discussionmentioning
confidence: 81%
“…Another autophagic induction marker P62, a multifunctional ubiquitin-binding protein, was selectively degraded by autophagy, and its expression was negatively correlated with the autophagy activity [27,28]. Similarly, Li et al also observed that the LC3II/LC3I ratio was significantly increased, and the expression of polyubiquitinbinding protein p62 was significantly decreased in the GT from the hypospadias male fetuses [29], indicating that exposure to DBP during pregnancy inhibited cell apoptosis and promoted cell autophagy in the GT of fetal male rats, thereby resulting in the formation of hypospadias. Subsequently, expressions of PERK-eIF2a pathway-related proteins were examined in the GT of hypospadias fetal male rats, presenting an increased expression pattern of p-PERK, p-eIF2a and ATF4.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, apoptosis plays a key role during the development of the male genitalia ( 51 , 69 , 70 ). Previous studies have proposed that the suppression of apoptotic-related genes can give rise to hypospadias ( 71 , 72 ). For instance, reduced apoptosis is observed in finasteride-induced hypospadiac rats through the MAPK/ERK signaling pathway ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a key cellular process for maintaining homeostasis, and involves Open Journal of Apoptosis the degradation of subcellular components [16] [17]. During this process, cellular components reach lysosomes for degradation [18]. It has been documented that phthalates can cause autophagic cell death with mitochondrial effects [19].…”
Section: Autophagymentioning
confidence: 99%